Fikih Indonesia dalam Perspektif Pemikiran Hasbi Ash-Shidieqy dan Hazairin: Transformasi Hukum Islam Dalam Impelementasi Hukum di Indonesia - Nada, Syifaun; Dani, Rahma Nur (Jurnal Syariah dan Hukum Komparatif, 2022)
Ash-Shiddieqy’s introduction of the term Indonesian fiqh was a compromise between Indonesian nationalism and Muslim reformism. By making Indonesian customs one of the sources of Indonesian fiqh. His conceptualization of “Indonesian fiqh”, through his immersion in classical Arabic texts and the writings of later reformers from the Middle East, and Hazairin’s emphasis on the role of particular cultural circumstances in shaping the Islamic content of Indonesian law, both show a comparable comparison. initiatives in the 1980s and 1990s. All of these writing initiatives continue to be the backdrop for legal discussion and debate among Indonesian Muslim intellectuals in the early twenty-first century. Indonesian fiqh can be interpreted as a concept of fiqh that is more locally based in Indonesia. Hasbi As-Shiddiqi and Hazairin are the two figures who initiated the Indonesian model of Fiqh, in addition to other scholars. Hasbi Hasbi was one of the reformers who offered his ideas comprehensively, starting from his concept of “Indonesian Jurisprudence”, to legal reform that includes both principles and methods. Meanwhile, Hazairin proposed the development of a new inheritance system which was interpreted and elaborated based on the scriptural perception of the Qur’an and Sunnah that it was not a patrilineal system, but a bilateral one, namely the family model